The selfish gene - Dawkins, Richard, 1941- (Oxford : Oxford University Press, 2016)
Examines the biology of selfishness and altruism in light of Darwin's Theory of Evolution.
Includes bibliographical references (p. 359-446) and index.
Adult
Adult
Keywords: Evolution (Biology); Genetics; Sociobiology; Evolution; Genetics; Sociobiology